HIV risk and influence factors among MSM who had sought sexual partners in core venues: a continuous sentinel surveillance in 2010–2022 - Yang, Zijie; Wei, Lan; Xu, Zhongliang; Li, Simei; Xing, Yiwen; Zhang, Yan; Yuan, Yuan; Liu, Shaochu; Xie, Wei; Tan, Wei; Ye, Wei; Tan, Jingguang; et al. (Frontiers in Public Health, 2024)
BackgroundSeeking sexual partners in men who have sex with men (MSM) venues has been regarded as a high-risk behavior for HIV among MSM. Nevertheless, with the implementation of venue-based interventions and the change in the way MSM seek sexual partners, the continued status of MSM venues as the HIV risk factor remains inconclusive. This study endeavors to delve into this ambiguity by examining the MSM sexual contact network (SCN) as a foundation.MethodsA series of cross-sectional surveys were conducted in Shenzhen in the period 2010–2022. MSM sexual contact network and venue network were acquired, and network metrics were employed to identify core MSM and core venues. We compared the risk of HIV and risk behaviors between MSM who sought sexual partners in core venues and those who did not, with subgroup analyses based on different time periods.ResultsThe overall HIV prevalence among the 4,408 MSM surveyed in this study was 14.6%. Notably, 17 core venues were identified out of the 68 reported MSM venues, with 1,486 MSM who had sought sexual partners in core venues. These MSM had significantly higher risk of HIV and were more likely to take HIV testing and receive intervention services. Subgroup analyses showed that the heightened HIV risk associated with seeking partners in core venues was specific to the period 2010–2014, while HIV testing and service access remained consistently higher across all-period subgroups. Multiple sexual partners, seeking partners in core venues, receptive or both sexual roles, drug abuse, absence of HIV test, unprotected anal intercourse (UAI), and lower education levels were associated with elevated HIV risk among MSM.ConclusionFollowing the implementation of differentiated venue-based interventions, the risk of HIV among MSM who had sought sexual partners in core venues decreased to a level comparable to that of MSM who had not. The accessibility of HIV testing and intervention services remains uneven between MSM who had sought sexual partners in core venues and those who had not. As the Internet sex-seeking behavior gains prevalence among MSM, strategic adjustments of public health resource allocation may be necessary to address this imbalance.